Assessment of Retinal Nerve Fiber Layer Thickness Strabismic and Anisometropic Amblyopia Cases - Medine Aslı Yıldırım; Burak Erden; Mustafa Elçioğlu (Bagcilar Medical Bulletin, 2025)
Objective: The aim of this study was to determine whether differences exist in retinal nerve fiber layer (RNFL) thickness between amblyopic eyes and non-amblyopic eyes of patients with strabismic amblyopia and anisometropic amblyopia using optical coherence tomography (OCT), as well as healthy eyes in a control group. Method: Thirty-six cases of unilateral anisometropic amblyopia, 40 cases of unilateral amblyopia with strabismus, and 42 healthy individuals were included. Patient history, demographic characteristics, and mean RNFL thickness values across quadrants were recorded using OCT. Results: A total of 118 participants were enrolled in the study, comprising 54 males and 64 females, with an average age of 16.25±9.05 years. Analysis of mean and quadrant RNFL thickness values revealed no statistically significant differences between amblyopic eyes, non-amblyopic eyes, and the control group (p>0.05). Similarly, there was no significant variation in RNFL thickness in the amblyopic eyes of patients with strabismic and anisometropic amblyopia compared to their non-amblyopic eyes or to the control group (p>0.05). However, participants with anisometropic amblyopia had a thicker mean RNFL when compared to those with strabismic amblyopia (p>0.05). Although there was a tendency for increased RNFL thickness across all quadrants in individuals with anisometropic amblyopia, this difference did not reach statistical significance (p<0.05). Conclusion: RNFL thickness was found to be similar in amblyopic and normal eyes. While existing studies have highlighted the impact of amblyopia on the RNFL, further investigations that consider additional factors are warranted.